A New Electromagnetic Model for Determining the Speed of Photon Absorption in a Photocatalytic Process for Wastewater Treatment (2019)
In the following work a new mode of operation is presented, as a continuation of the research developed on the elaboration of an electromagnetic model for the determination of the speed of photonic absorption in a solar collector in V (V - collector) (Ramos et al. 2017). The electromagnetic characteristics of the fluid in the suspension will be studied, such as electric permittivity, magnetic permeability, electrical conductivity and frequency of incident light. Likewise, the time variable is included as the innovation in the model to obtain the factors of the phase and the attenuation of the electromagnetic wave that penetrates the suspending medium and the photocatalytic process. For the model, an opto-geometric analysis of the V collector was used, which was studied and contrasted with the literature (Bandala et al. 2004).